Mengembangkan Etika Dalam Kehidupan Sehari-Hari Di Persekutuan Anak Remaja (Par) Gki Jemaat Efata Malanu, Kota Sorong - Natasya Virginia Leuwol; Windy Wonmaly; Marcya Vanessa Glory Pical; Graycella Mellitasari Habibi; Marlin Ruth Korwa; Gheatre Lesly Siahaya (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This Community Service Activity (PKM) was conducted by third-semester students (Class 3A) of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Universitas Victory Sorong, at the Youth Fellowship (PAR) of GKI Efata Malanu Congregation, Sorong City, on Sunday, November 7, 2025. The activity aimed to instill an understanding of the importance of ethics in daily life among church children and youth, as well as to provide students with opportunities to apply character education values in real community contexts. The methods used included interactive counseling, group discussions, value-based educational games, storytelling, and reflective sessions.The results of the activity indicated an increase in participants’ understanding of ethical values such as responsibility, honesty, politeness, and respect for others. Participants also demonstrated positive behavioral changes in their social interactions throughout the activity. For students, the program provided a practical learning experience in applying ethical and character education theories through participatory learning approaches. In addition to strengthening pedagogical and communication skills, this activity also fostered collaboration between the university and the church in shaping young generations to be ethical, faithful, and responsible individuals.